THE ANALYSIS OF MADRASAH SUPERVISORS' COMPLIANCE AND COMPETENCE EFFECT ON THEIR PERFORMANCE DEVELOPMENT - Supadi, Supadi (EARR (Educational Administration Research and Review), 2017)
This study aims to: (1) know the description of the competence of the supervisor of madrasah (2) know the description of the compliance adherence level of the madrasah supervisor (3) know the performance of the madrasah supervisor on the madrasah and (4) develop the Supervisor’s competency of madrasah by adding competence of Islamic education in Jakarta, Bogor, Depok, Tangerang and Bekasi. This research is a comparative causal research (Causal-Comparative Research) with the unit of analysis studied is the supervisor of madrasah located in Jakarta, Bogor, Depok, Tangerang and Bekasi. This study included research survey using questionnaire and in-depth interview with a total sample of 150 madrasah supervisors. The test equipment used in this study uses the classical assumption test which includes normality test, multicolonierity test, heteroscedasticity test and linearity test. The method of data analysis used is simple regression analysis and multiple regression analysis. The result of this research shows that based on the result of path analysis can be obtained the effect of inter-variables as follows: there is a positive influence of supervisor's compliance and competence to supervisor's performance.